Implementing sport policy : organisational perspectives on the UK sport system / edited by Marc Keech, Iain Lindsey and John Hayton. - Keech, Marc; Lindsey, Iain; Hayton, John (Routledge research in sport business and management., 2024)
This volume critically examines the roles and contributions of different organisations in the implementation of sport policy in the UK, and therefore provides an important guide to the complexities of implementing sport policy and of achieving policy goals through, and for, sport.